Neoadjuvant Nivolumab Plus Gemcitabine/Cisplatin Chemotherapy in Muscle-Invasive Urothelial Carcinoma of the Bladder - Kim, Hongsik; Jeong, Byong Chang; Hong, Joohyun; Kwon, Ghee Young; Kim, Chan Kyo; Park, Won; Pyo, Hongryull; Song, Wan; Sung, Hyun Hwan; Hong, Jung Yong; Park, Se Hoon (Cancer research and treatment, 2023)
Purpose The activity and safety of neoadjuvant nivolumab plus gemcitabine/cisplatin (N+GC) were tested in patients with muscle-invasive bladder urothelial carcinoma (MIBC).Materials and Methods In a prospective phase II trial, patients with cT2-T4a N0 MIBC who were eligible for cisplatin and medically appropriate to undergo radical cystectomy (RC) were enrolled. Treatment with nivolumab 3 mg/kg on days 1 and 15 plus GC (cisplatin 70 mg/m2 on day 1, and gemcitabine 1,000 mg/m2 on days 1, 8, and 15) was repeated every 28 days up to 3 or 4 cycles, depending on the surgery schedules. The primary endpoint was pathologic complete response (pCR, ypT0). Secondary endpoints included pathologic downstaging (≤ ypT1), disease-free survival (DFS), and safety.Results Between September 2019 and October 2020, 51 patients were enrolled. Neoadjuvant N+GC was well tolerated. Among 49 patients who completed neoadjuvant N+GC, clinical complete response (cCR) was achieved in 59% of intent-to-treat (ITT) population. RC was performed in 34 (69%) patients. pCR was achieved in 24% (12/49) of ITT population and 35% (12/34) of RC patients. Median DFS was not reached. Over a median follow-up of 24 months, 12 patients experienced disease recurrence and were treated with palliative therapy or surgery. Although 12 patients declined surgery and were treated with concurrent chemoradiotherapy, DFS was longer in patients with cCR after neoadjuvant therapy than those without. Preoperative programmed death-ligand 1 (PD-L1) did not correlate with pCR or pathologic downstaging rates.Conclusion Neoadjuvant N+GC was feasible and provided meaningful pathologic responses in patients with MIBC, regardless of baseline PD-L1 expression (ONO-4538-X41; CRIS.nih.go.kr, KCT0003804).